ULF foreshock under radial IMF: THEMIS observations and global kinetic simulation Vlasiator results compared. Issue 10 (28th October 2015) - Palmroth, M.; Archer, M.; Vainio, R.; Hietala, H.; Pfau‐Kempf, Y.; Hoilijoki, S.; Hannuksela, O.; Ganse, U.; Sandroos, A.; Alfthan, S. von; Eastwood, J. P.
Abstract: For decades, monochromatic large‐scale ultralow frequency (ULF) waves with a period of about 30 s have been observed upstream of the quasi‐parallel bow shock. These waves typically propagate obliquely with respect to the interplanetary magnetic field (IMF), while the growth rate for the instability causing the waves is maximized parallel to the magnetic field. It has been suggested that the mechanism for the oblique propagation concerns wave refraction due to the spatial variability of the suprathermal ions, originating from theE ×B drift component. We investigate the ULF foreshock under a quasi‐radial IMF with Vlasiator, which is a newly developed global hybrid‐Vlasov simulation solving the Vlasov equation for protons, while electrons are treated as a charge‐neutralizing fluid. We observe the generation of the 30 s ULF waves and compare their properties to previous literature and multipoint Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft observations. We find that Vlasiator reproduces the foreshock ULF waves in all reported observational aspects. We conclude that the variability of the density and velocity of the reflected back streaming ions determines the large‐scale structure of the foreshock, which affects the wave frequency, wavelength, and oblique propagation. We conclude that the wave refraction may also be at work for radial IMF conditions, which has earlier been thought of as an exception to the refraction mechanism due to the smallE ×B drift component. We suggest that additional refraction may be caused by the large‐scale spatial variability of the density and velocity of the back streaming ions. Key Points: The paper concerns ULF wave properties under quasi‐radial IMF Global hybrid‐Vlasov simulation results agree with known foreshock properties and observations We suggest a mechanism for oblique wave propagation based on spatial variation of back streaming ions